Model-Assisted Analysis of Sugar Metabolism throughout Tomato Fruit Development Reveals Enzyme and Carrier Properties in Relation to Vacuole Expansion. Issue 8 (19th August 2014) - Beauvoit, Bertrand P.; Colombié, Sophie; Monier, Antoine; Andrieu, Marie-Hélène; Biais, Benoit; Bénard, Camille; Chéniclet, Catherine; Dieuaide-Noubhani, Martine; Nazaret, Christine; Mazat, Jean-Pierre; Gibon, Yves
Abstract : A kinetic model combining enzyme activities and subcellular compartmentation was built to analyze the storage and interconversion of sugars in developing tomato fruit. This work shows that tonoplast carriers, sucrose hydrolysis, and accumulation of organic acids are major contributors to the vacuole expansion and the metabolic reprogramming that occur during early development. Abstract: A kinetic model combining enzyme activity measurements and subcellular compartmentation was parameterized to fit the sucrose, hexose, and glucose-6-P contents of pericarp throughout tomato ( Solanum lycopersicum ) fruit development. The model was further validated using independent data obtained from domesticated and wild tomato species and on transgenic lines. A hierarchical clustering analysis of the calculated fluxes and enzyme capacities together revealed stage-dependent features. Cell division was characterized by a high sucrolytic activity of the vacuole, whereas sucrose cleavage during expansion was sustained by both sucrose synthase and neutral invertase, associated with minimal futile cycling. Most importantly, a tight correlation between flux rate and enzyme capacity was found for fructokinase and PPi-dependent phosphofructokinase during cell division and for sucrose synthase, UDP-glucopyrophosphorylase, and phosphoglucomutase during expansion, thus suggesting an adaptation of enzyme abundance to metabolic needs. In contrast, for most enzymes, flux rates varied irrespectively of enzyme capacities, and most enzymes functioned at <5% of their maximal catalytic capacity. One of the major findings with the model was the high accumulation of soluble sugars within the vacuole together with organic acids, thus enabling the osmotic-driven vacuole expansion that was found during cell division.